(untitled) (Research, Society and Development, 2025)
Objective: To map the difficulties faced by educators and students in science laboratories within the teaching-learning process. Method: A scoping review following the JBI protocol, utilizing Boolean operators (AND/OR) across nine databases. Inclusion criteria: studies published between 2020–2025 focusing on challenges in natural/health science laboratories. Exclusion criteria: studies involving virtual laboratories, animal models, or non-empirical research. Results: Twelve studies revealed interconnected challenges in infrastructure, insufficient educator training, inadequate management, and lack of biosafety protocols. Discussion: Material precariousness undermines experimental work, perpetuating a theory-practice disconnect. Deficits in educator training and excessive workload hinder the overcoming of these barriers, creating a cycle of pedagogical insufficiency. Conclusion: The difficulties are systemic and require integrated interventions in infrastructure, educator training, and management policies to establish functional laboratory environments.